Pertarungan Harga dan Kualitas Pelayanan: Strategi Gojek Menjaga Konsumen Jakarta - Febrianti Natalia Galung; Kartika Yuliantari (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This studies targets to analyze the effect of carrier best and rate on GOJEK user pleasure in DKI Jakarta. GOJEK, as one in all the biggest on-line transport applications in Indonesia, faces stiff competition from different agencies supplying similar services. consequently, it's miles vital for GOJEK to constantly improve its carrier best and offer competitive prices to maintain its dominant function. This studies makes use of quantitative methods with records collection thru questionnaires disbursed to GOJEK customers in DKI Jakarta. The sampling technique used was stratified sampling, with a complete of 124 respondents. The collected statistics had been analyzed using validity, reliability, classical assumption exams, and more than one linear regression analysis. The outcomes confirmed that provider high-quality and rate have a good sized impact on GOJEK person pride. The provider best variable has a nice affect on person satisfaction, as well as the price variable. The F test results show that service fine and fee simultaneously have a sizeable impact on person delight with a coefficient of dedication of 41.four%, which indicates that 41.4% of the version in person pride can be explained by means of service nice and charge. primarily based on these findings, GOJEK is recommended to retain improving its service exceptional and providing competitive costs to increase consumer pleasure and preserve customer loyalty amid more and more fierce opposition